2021
DOI: 10.3390/land10030269
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Characteristics of Precipitation and Its Relationship with Land Use/Cover Change on the Qinghai-Tibet Plateau, China

Abstract: The Qinghai-Tibet Plateau (QTP) is an area sensitive to global climate change, and land use/land cover change (LUCC) plays a vital role in regulating climate system at different temporal and spatial scales. In this study, we analyzed the temporal and spatial trend of precipitation and the characteristics of LUCC on the QTP. Meanwhile, we also used the normalized difference vegetation index (NDVI) as an indicator of LUCC to discuss the relationship between LUCC and precipitation. The results show the following:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 73 publications
0
12
1
Order By: Relevance
“…Our study also supports this view that TP has become wetter during 1982-2015, since the increase of P total and P freq has been observed in most area of TP (Figures 1e 1h 1k and 1n). We further found an increasing trend (28.7 mm/decade) of spring and summer P total for CMFD during 1982-2015 (Figure 1h), which was higher than previous finding of 10.4 mm/decade during 1967-2016 (Zhang & Zhou, 2021), suggesting more heavy precipitation alterations in recent years. Moreover, we found that P total exhibited more proportion of significantly increased pixels than P freq (18.9% vs. 9.9% for CMFD, 62.5% vs. 56.8% for CRU) (Figures 1f 1i 1l and 1o), possibly suggesting that larger precipitation events have been occurring in TP (Guo et al, 2020b;Q.…”
Section: 2contrasting
confidence: 63%
“…Our study also supports this view that TP has become wetter during 1982-2015, since the increase of P total and P freq has been observed in most area of TP (Figures 1e 1h 1k and 1n). We further found an increasing trend (28.7 mm/decade) of spring and summer P total for CMFD during 1982-2015 (Figure 1h), which was higher than previous finding of 10.4 mm/decade during 1967-2016 (Zhang & Zhou, 2021), suggesting more heavy precipitation alterations in recent years. Moreover, we found that P total exhibited more proportion of significantly increased pixels than P freq (18.9% vs. 9.9% for CMFD, 62.5% vs. 56.8% for CRU) (Figures 1f 1i 1l and 1o), possibly suggesting that larger precipitation events have been occurring in TP (Guo et al, 2020b;Q.…”
Section: 2contrasting
confidence: 63%
“…To further quantitatively analyze the relationship between NDVI and climate factors, the correlation analysis method is adopted to calculate the correlation coefficient of NDVI, annual average temperature, and precipitation data pixel by pixel [57,58]. The calculation formula is:…”
Section: Correlation Analysis Methodsmentioning
confidence: 99%
“…In Bhutan, the total area covered by forest increased markedly compared to other land cover types in three decades (1990 to 2010), representing a rare example of environmental transformation due to climate change affecting the snow leopard landscape [87]. A contrasting situation of land degradation, deforestation, and habitat fragmentation occurred in all other range countries (Table 3) in the snow leopard landscape [88][89][90]. The Belt and Road Initiative (BRI), which was initiated by the Chinese government in 2013 to enhance regional connectivity and so economic development, is the largest infrastructure project in human history [102].…”
Section: Land Use and Land Cover Changesmentioning
confidence: 99%